Effects of anatolian propolis and hypertonic saline combination nasal spray on allergic rhinitis symptoms: a prospective, multicenter study - Cingi, Cemal; Bayar Muluk, Nuray; Çukurova, İbrahim; Dündar, Rıza; Osma, Üstün; Bal, Cengiz; Zirek, Alaattin; Budak, Ali; Resuli, Ali Seyed; Selimoğlu, Asif; Tanuğur Samancı, Aslı Elif; Karaoğullarından, Ayşe; et al. (My University, 2024)
Objectives: This study aimed to evaluate how Rhinapi nasal spray affects symptoms of allergic rhinitis. Methods: In this prospective, multicenter, observational study, 10,000 patients (comprising 5028 males and 4972 females) exhibiting symptoms of allergic rhinitis (namely, nasal discharge, sneezing, nasal itching, and nasal obstruction) from different centers in different regions of Turkey were enrolled in the study between March 2022 and March 2023. All the patients wanted to participate in the study and were administered Rhinapi one puff to each nostril three times a day, for a period of 3 weeks. Total symptom scores, quality of life (QoL) scores, and otolaryngological examination scores were evaluated before and 3 weeks after treatment. Results: The scores for discharge from the nose, sneezing, nasal pruritus, and blockage of the nose all indicated improvement when compared to pre-medication and post-medication. This difference achieved statistical significance (P < .001). The mean total symptom score fell following treatment (P < .001): whilst the score was 11.09 +/- 3.41 before administering Rhinapi; after administration, the average score was 6.23 +/- 2.41. The mean QoL scores also altered after medication (P < .001), improving from a mean value of 6.44 +/- 1.55 to a mean of 7.31 +/- 1.24. Significant improvement was also noted in the scores for conchal color and degree of edema after the treatment had been administered (P < .001). Conclusion: The study demonstrates that Rhinapi nasal spray decreases total symptom scores, and results in improved QoL and otolaryngological examination scores. Propolis spray may be recommended for patients with allergic rhinitis alongside other treatments.
Keywords: Propolis; Allergic Rhinitis; Nasal; Total Symptom Score